Basics of Ultrasound and Its Use in Medicine: A Review Article - Haqiqullah, Chardiwal; Shakib, Zalmai Ahmad; Nasratullah, Zubair; Ghafar, Sherzad Abdul; Jan, Adil Ali (Journal for Research in Applied Sciences and Biotechnology, 2024)
This paper aims to present the basics of ultrasound and its application in medicine. It introduces parts of an ultrasound machine and gives information about the transducer, which is the main component of an ultrasound machine. The- image producing process and ultrasound wave characteristics are explained. Different methods for two- and three-dimensional imaging of the human anatomy are demonstrated. Ultrasound wave penetration, attenuation, acoustic impedance, and resolution are stated. Different types of diseases and different types of ultrasounds for their diagnosis are presented.